Truncated ternary multipliers. Issue 2 (1st March 2015) - Parhami, Behrooz
Abstract : Balanced ternary number representation and arithmetic, based on the symmetric radix‐3 digit set {−1, 0, +1}, has been studied at various times in the history of computing. Among established advantages of balanced ternary arithmetic are representational symmetry, favourable error characteristics and rounding by truncation. In this study, we show an additional advantage: that of lower‐error truncated multiplication with the same relative cost reduction as in truncated binary multipliers.